New and conventional media to senior high school student’s reading motivation - Alda, Rivika; Lopez, Jessa Rose; Alburan, Kent Vincent (International Journal of Evaluation and Research in Education (IJERE), 2024)
Motivation has long been established as an important factor that affects reading among students. With the advent of technology, reading motivation has become more nuanced as new reading media alongside conventional media surfaced. The study explored the relationship between senior high school students’ new and conventional media preferences and their reading motivation. A descriptive correlational research design was employed to analyze the data and determine correlations between variables. Results revealed that students generally have a stronger preference for books (physical books, school books, and pocketbooks) as reading media. Students also have a stronger preference for reading academic texts in print formats. In terms of the amount of time spent on reading electronic and print texts, students generally spend longer time reading electronic texts. The results also showed higher intrinsic motivation to read than extrinsic motivation among students. Finally, significant positive relationships were found between most intrinsic motivation scales and students’ new media preferences. Few significant positive relationships were found between extrinsic motivation scales and students’ new media preferences. Implications of these findings highlighted the need to utilize both conventional and new media and consider students’ preferences vis-à-vis classroom reading tasks.